2011
DOI: 10.1002/qj.905
|View full text |Cite
|
Sign up to set email alerts
|

Satellite cloud and precipitation assimilation at operational NWP centres

Abstract: The status of current efforts to assimilate cloud-and precipitation-affected satellite data is summarised with special focus on infrared and microwave radiance data obtained from operational Earth observation satellites. All global centres pursue efforts to enhance infrared radiance data usage due to the limited availability of temperature observations in cloudy regions where forecast skill is estimated to strongly depend on the initial conditions. Most systems focus on the sharpening of weighting functions at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
100
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 83 publications
1
100
1
1
Order By: Relevance
“…Increasingly, NWP centres are making use of these observations in cloudy and precipitating situations as well as in clear skies (e.g. Bauer et al, 2011). This helps to infer water vapour information in cloudy and precipitating areas and it also gives the possibility to assimilate the cloud and precipitation itself.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, NWP centres are making use of these observations in cloudy and precipitating situations as well as in clear skies (e.g. Bauer et al, 2011). This helps to infer water vapour information in cloudy and precipitating areas and it also gives the possibility to assimilate the cloud and precipitation itself.…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall forecast from the NWP models has improved over the last decades with the continuous progress in both numerical model and data assimilation techniques [Benedetti et al, 2005;Bauer et al, 2011;Lopez, 2011]. However, still there is a need to explore the new opportunities for model development through the use of data from active and passive sensors jointly [Benedetti et al, 2005;Pu et al, 2002;Bauer et al, 2011]. Rainfall assimilation is considered as one of the important approaches to improve the weather forecasts, because rainfall observation includes the atmospheric information in terms of humidity, temperature, and winds and also contributes to the model atmospheric energy budget [Marecal and Mahfouf, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Several numerical modeling studies have shown that rainfall data improved the weather forecast [e.g., Bauer et al, 2011;Krishnamurti et al, 1991Krishnamurti et al, , 1993Lopez, 2011;Puri and Miller, 1990;Treadon, 1996;Tsuyuki, 1997;Zou and Kuo, 1996;Zupanski and Mesinger, 1995]. A number of sensitivity tests have been performed for rainfall assimilation at various forecast/research centers like in European Centre for Medium-Range Weather Forecasts [Heckley et al, 1990;Puri and Miller, 1990], Florida State University [Krishnamurti et al, 1984[Krishnamurti et al, , 1993Tsuyuki, 1997], and National Centers for Environmental Prediction (NCEP) [Treadon, 1996[Treadon, , 1997.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cloud water and precipitation from satellite sensors are now routinely ingested into numerical weather prediction (NWP) models (Bauer et al, 2011). Soil moisture observations are at the point of entering into operational NWP assimilation schemes (Rosnay et al, 2011).…”
Section: Introductionmentioning
confidence: 99%